Research and Practice of the Management and Protection Mode of Yantai Mountain National Marine Park - LI Feng; WANG Shunzhou; FAN Yifeng; WANG Na; LYU Renzhong; LIN Haibo; LU Yuan; CHI Shoufeng (Haiyang Kaifa yu guanli)
The National Marine Park is an effective mean of protecting and managing marine resources in China. However, deficiencies in management organizational capacity, social engagement capacity, and system-based management service measures in the Yantai Mountain National Marine Park have significantly impacted management efficiency and the achievement of conservation goals. Drawing upon and incorporating relevant work experiences both domestically and internationally, this paper, based on the implementation of the management capacity-building project in the Yantai Mountain National Marine Park, explores the “Joint construction and Co-management” model of marine park management involving the government, community, and enterprises. Post-implementation, notable advantages in management, ecological benefits, and social benefits have emerged. Consequently, this study aims to provide insights and a reference framework for the construction and management of national marine parks across China through the research and application of the management and protection model employed in the Yantai Mountain National Marine Park.